Galois Ring GR (2(3),8) Dependent 24 x 24 S-Box Design: An RGB Image Encryption Application - Shah, Tariq; Ali, Asif; Khan, Majid; Farooq, Ghazanfar; Andrade, Antonio Aparecido de [UNESP] (Springer, 2020)
An S-box is based on Boolean functions which are essentially the foundation of symmetric cryptographic systems. The Boolean functions are used for S-box designing in block ciphers and exploited as nonlinear components. Boolean functions with optimal nonlinearity and upright cryptographic stuffs play a significant role in the design of block ciphers. Traditionally 8x8 S-box is a 16x16look up table over Galois field GF and has 112 feasible upper bonds for nonlinearity. A 24x24 S-box over Galois field GFis not viable as the computer memory does not support it. In this paper for the construction of 24x24S-box a rout is adopted via maximal cyclic subgroup of the multiplicative group of units of Galois ring GR The newly constructed S-box has much higher confusion capability than any of 8x8 S-box. To judge the impact of this new 24x24 S-box an RGB color image encryption application is demonstrated. Initially, in the proposed encryption scheme we use 24x24 S-box for confusion in RGB channels of plain image, however for diffusion linear permutation P= is operated and then by the use of exclusive-or an encrypted image is obtained. Thus, we introduce a novel technique by which 24 binary bits are divided into 3 bytes and each one deals R, G and B channel of the color image separately. A comparison with chaos and DNA based image encryption schemes shows the performance results of this novel RGB image encryption and observed as meeting the standard optimal level. Hence this 24x24 S-box dependent encryption method replaces 8x8S-box based RGB color image encryption scheme.
Keywords: n x n S-box; Nonlinearity; Galois ring; Maximal cyclic subgroup; RGB Image encryption